Non-alcoholic Fatty liver Disease in Patients with Psoriasis - Therapeutic Implications - Kłujszo, Elżbieta Halina; Parcheta, Piotr; Witkowska, Anna B.; Kręcisz, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Non-alcoholic fatty liver disease (NAFLD) is the most common liver pathology in the West. Psoriatic patients are at higher risk of having NAFLD, and at higher risk of experiencing the more severe form of the disease, with poorer outcomes. The components of the metabolic syndrome – obesity, lipid abnormalities, hypertension, and type 2 diabetes – significantly correlate with NAFLD progression. The inflammatory state present in psoriasis plays a significant role in development of NAFLD and the metabolic syndrome. All patients with psoriasis and insulin resistance and risk factors for metabolic syndrome should also been screened for NAFLD, and planning of the treatment options should always take into consideration the possible risks for the liver, especially in patients with NAFLD.